Vliv průměru a hloubky dírky v píšťale na barvu a směrovost - Borovičková, Barbora (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2023)
Práce zkoumá vliv průměru a hloubky tónových otvorů zobcové flétny na barvu a směrovost výsledného tónu. Pro měření a následnou datovou analýzu bylo vyrobeno devět prototypů korpusu flétny ze třech různých materiálů a rozdílnou tloušťkou stěny. V průběhu měření byly do prototypů vrtány otvory s různým průměrem. Díky tomuto postupu se povedlo oddělit žádoucí vlivy od nežádoucích. Naměřená data byla analyzována v prostředí Matlab.

This bachelor’s thesis examines the influence of the diameter and depth of the holes in the recorder on the timbre and directionality of the resulting tone. For measurements and subsequent data analysis, nine flute body prototypes were made from three different materials and with three different wall thicknesses. During the measurement, holes with different diameters were drilled into the prototypes. Thanks to this procedure, it was possible to separate desirable influences from undesirable ones. The measured data were analyzed in the Matlab environment.
The influence of the diameter and depth of the hole in the whistle on the timbre and directionality
Keywords: Analýza; Barva tónu; Hloubka otvoru; Píšťaly; Průměr otvoru; Směrovost; Spektrum; Zobcová flétna; Analysis; Depth of the hole; Diameter of the hole; Directionality; Recorder; Spektrum; Timbre; Tone hole; Whistles